2017
DOI: 10.1128/jb.00252-17
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the Regulon of AphB and Its Essential Roles in LuxR and Exotoxin Asp Expression in the Pathogen Vibrio alginolyticus

Abstract: In species, AphB is essential to activate virulence cascades by sensing low-pH and anaerobiosis signals; however, its regulon remains largely unknown. Here, AphB is found to be a key virulence regulator in, a pathogen for marine animals and humans. Chromatin immunoprecipitation followed by high-throughput DNA sequencing (ChIP-seq) enabled the detection of 20 loci in the genome that contained AphB-binding peaks. An AphB-specific binding consensus was confirmed by electrophoretic mobility shift assays (EMSAs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The LTTR protein MetR has been shown to be involved in QS regulation in response to methionine metabolism in V. harveyi (31). AphB, a low-pH-and oxygen-responsive LTTR protein (32,33), regulates QS by directly binding to the luxR promoter and controlling LuxR expression at the transcriptional level in V. alginolyticus (25). Moreover, identification of the oxidativestress-responsive SoxR (34) and the feast/famine regulatory protein AsnC (35) as being involved in QS regulation also suggested that various physiological signals might affect QS regulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LTTR protein MetR has been shown to be involved in QS regulation in response to methionine metabolism in V. harveyi (31). AphB, a low-pH-and oxygen-responsive LTTR protein (32,33), regulates QS by directly binding to the luxR promoter and controlling LuxR expression at the transcriptional level in V. alginolyticus (25). Moreover, identification of the oxidativestress-responsive SoxR (34) and the feast/famine regulatory protein AsnC (35) as being involved in QS regulation also suggested that various physiological signals might affect QS regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The genes of 285 probable transcription factors were amplified from V. alginolyticus EPGS by using gene-specific primers (a subset of the primers are shown in Table 3) and cloned into the pTRG plasmid. The promoters of the V. alginolyticus aphA and luxR genes were amplified using primers specific to these promoters (Table 3) and inserted into the reporter vector pBXcmT, as previously described (25,26). The E. coli XL1-Blue MRF9 kanamycin-resistant (Km r ) strain was used for propagating all pBXcmT and pTRG recombinant plasmids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, Vibrio parahaemolyticus is a common cause of foodborne disease (Sakata, Yonekita, & Kawatsu, ), while Vibrio alginolyticus is implicated in wound infections and otitis. Vibrio alginolyticus was recently recognized as a human pathogen after excessive exposure to seawater (Gao et al., ). Vibrio fluvialis has been considered an emerging pathogen that induces foodborne diarrhea (Ramamurthy, Chowdhury, Pazhani, & Shinoda, ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were first extracted with phenol-chloroform and then precipitated with ethanol, and the pellets were dissolved in 30 μl of Milli-Q water. The preparation of the DNA ladder, electrophoresis, and DNA sequencing were performed as described previously (45, 46).…”
Section: Methodsmentioning
confidence: 99%